IS CLIMATE CHANGE A BLESSING OR CURSE? THE CHANGING CLIMATE INFLUENCE ON PLANT DISEASES AND PESTS DEVELOPMENT: A NARRATIVE STUDY. - Turyasingura, Benson; Katel, Shambhu; Chilumpha, Dean Gabriel; Tumwesigye, Wycliffe; Chavula, Petros (Student's Journal of Health Research Africa, 2024)
The study investigates the impact of climate change on the development of plant diseases and the emergence of novel plant diseases, the conditions for disease development, mitigation strategies, and adaptation strategies for pest control. Climate change and variability may have indirect effects on animal diseases that are more significant than direct consequences. However, there has been little focus on the impact of climate change on agriculture, particularly concerning insect pests; because rising temperatures hasten insect life cycles, migration, and nutrition. It is concluded that it is necessary to construct and reinforce barriers that stop the arrival of exotic infections, develop tools for quick diagnosis of novel diseases, and train technical personnel to use these techniques once they are in place.